2006
DOI: 10.1158/1541-7786.mcr-05-0172
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin Affects Components of the Chromosomal Passenger Complex and Induces Mitotic Catastrophe in Apoptosis-Resistant Bcr-Abl-Expressing Cells

Abstract: The Bcr-Abl oncoprotein plays a major role in the development and progression of chronic myeloid leukemia and is a determinant of chemotherapy resistance occurring during the blast crisis phase of the disease. The aim of this article was to investigate the possibility of combating the resistance to apoptosis caused by Bcr-Abl by inducing an alternative cell death process. As a model of chronic myeloid leukemia, we employed Bcr-Abl-transfected mouse progenitor 32D cells with low and high Bcr-Abl expression leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
67
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 81 publications
(73 citation statements)
references
References 51 publications
5
67
1
Order By: Relevance
“…High expression of Aurora A in leukemia cell lines and freshly isolated leukemia CML cells has been presented by Ochi T et al (Ochi et al, 2009). We also showed that the expression of BCR-ABL leads to the mislocalization of Aurora A in the chromosomal passenger complex (Wolanin et al, 2006). The importance of Aurora A-dependent signaling in CML has been shown in studies indicating that Aurora inhibitors seem to be very effective therapeutics for CML treatment (Gontarewicz et al, 2008), what will be discussed by us later.…”
Section: Aberrant Expression Of Mitotic Kinasessupporting
confidence: 64%
See 2 more Smart Citations
“…High expression of Aurora A in leukemia cell lines and freshly isolated leukemia CML cells has been presented by Ochi T et al (Ochi et al, 2009). We also showed that the expression of BCR-ABL leads to the mislocalization of Aurora A in the chromosomal passenger complex (Wolanin et al, 2006). The importance of Aurora A-dependent signaling in CML has been shown in studies indicating that Aurora inhibitors seem to be very effective therapeutics for CML treatment (Gontarewicz et al, 2008), what will be discussed by us later.…”
Section: Aberrant Expression Of Mitotic Kinasessupporting
confidence: 64%
“…In case of cancers with the defective p53 function, survivin silencing led to reduced mitotic arrest and enhanced polyploidy, what is a very unwanted and dangerous side-effect. Also in our studies, specific depletion of survivin by siRNA approach in CML cells with checkpoints defects, resulted in strong polyploidization and chromosomal instability (Wolanin et al, 2006). However, when we used a natural compound -curcumin, which has been shown as a broadly acting, very potent anticancer agent, we found that it affects the CPC proteins and induces mitotic catastrophe, however without polyploidization.…”
Section: Chromosomal Passenger Complex and Aurora Kinasesmentioning
confidence: 59%
See 1 more Smart Citation
“…2D, i-iii). To identify if they were associated with mitosis, these bortezomib-treated SNK-6 cells were examined by immunofluorescence with the MPM-2 antibody, which recognizes the mitosis-specific phosphorylated proteins, thus serving as a marker of mitotic cells (22). As expected, bortezomib induced an accumulation of MPM-2-positive cells among the SNK-6 cells with the chromosomes in total disarray.…”
Section: Bortezomib Induced Mitotic Catastrophe In Snk-6 Cellsmentioning
confidence: 76%
“…Such observations suggest that curcumin is a pharmacologically safe agent that may be used not only in cancer chemoprevention, but also in cancer therapy, either as a primary therapeutic agent or as an adjuvant to traditional chemotherapy. Although much of the research into the cancer-killing effects of curcumin has focused on its ability to induce apoptosis [2,3,6,7], curcumin has also been reported to induce nonapoptotic cell death through mitotic catastrophe [8,9] or autophagic cell death [10] in several types of cancer cells.…”
mentioning
confidence: 99%